GM-CSF: A Promising Target in Inflammation and Autoimmunity - Lee, Kevin MC; Achuthan, Adrian A; Hamilton, John A (ImmunoTargets and therapy, 2020)
The cytokine, granulocyte macrophage-colony stimulating factor (GM-CSF), was firstly identified as being able to induce in vitro the proliferation and differentiation of bone marrow progenitors into granulocytes and macrophages. Much preclinical data have indicated that GM-CSF has a wide range of functions across different tissues in its action on myeloid cells, and GM-CSF deletion/depletion approaches indicate its potential as an important therapeutic target in several inflammatory and autoimmune disorders, for example, rheumatoid arthritis. In this review, we discuss briefly the biology of GM-CSF, raise some current issues and questions pertaining to this biology, summarize the results from preclinical models of a range of inflammatory and autoimmune disorders and list the latest clinical trials evaluating GM-CSF blockade in such disorders.